2015
DOI: 10.1262/jrd.2015-015
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metritis and subclinical hypocalcemia on uterine involution in dairy cows evaluated by sonomicrometry

Abstract: The objective of this study was to examine the effects of metritis and subclinical hypocalcemia on reduction of uterine size in dairy cows using ultrasonography and sonomicrometry. Four piezoelectric crystals were implanted via laparotomy into the myometrium of the pregnant uterine horn of 12 pluriparous Holstein Friesian cows 3 weeks before the calculated calving date. Sonometric measurements were conducted daily from 2 days before parturition (= Day 0) until Day 14 after calving and then every other day unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 29 publications
(40 reference statements)
0
13
1
Order By: Relevance
“…On the other hand, although there was no significant difference in the detection rate of PVD, the detection rate was numerically higher at 7 wk; it was speculated that the prolonged endometrial inflammation is causing continued excretion of purulent discharge from the uterus. Furthermore, it has been reported that serum Ca concentration is associated with a neutrophil function [ 33 ] and uterine involution [ 34 ]; however, the blood concentrations of iCa and tCa did not affect endometrial inflammation convergence in our study. These discrepancies between previous studies and the present study may result from the difference in the classification method.…”
Section: Discussioncontrasting
confidence: 77%
“…On the other hand, although there was no significant difference in the detection rate of PVD, the detection rate was numerically higher at 7 wk; it was speculated that the prolonged endometrial inflammation is causing continued excretion of purulent discharge from the uterus. Furthermore, it has been reported that serum Ca concentration is associated with a neutrophil function [ 33 ] and uterine involution [ 34 ]; however, the blood concentrations of iCa and tCa did not affect endometrial inflammation convergence in our study. These discrepancies between previous studies and the present study may result from the difference in the classification method.…”
Section: Discussioncontrasting
confidence: 77%
“…Specifically, cows with delayed uterine involution have reduced CD2 + , CD4 + , CD8 + and B-cells in peripheral blood. The duration of uterine involution is positively associated with uterine disease, and as such depletion of these cellular subpopulations may be causative of delayed uterine involution, increasing the risk of uterine disease (Heppelmann et al, 2015; Melendez et al, 2004). However, these studies did not quantify changes to lymphocyte populations during the prepartum period which may predispose to delayed uterine involution and subsequent uterine disease.…”
Section: Discussionmentioning
confidence: 99%
“…Increased size of the uterus can be considered as swelling due to inflammation (Kauffold et al., ). Thus, it may cause, as in other species, that is in beef heifer and dairy cows (Heppelmann et al., ; Savc, Kenny, & Beltman, ), prolonged uterine involution and thereby interfere with subsequent fertility.…”
Section: Effect Of Farrowing Duration and Pds On Sow Fertilitymentioning
confidence: 99%